2021
DOI: 10.1002/maco.202112516
|View full text |Cite
|
Sign up to set email alerts
|

Tempering kinetics and corrosion resistance of quenched and tempered AISI 4130 medium carbon steel

Abstract: The kinetics and the effects of tempering on the corrosion resistance of AISI 4130 steel were studied. The tempering activation energy was close to that for the diffusion of C in α-iron. This implies that the tempering kinetics in this steel is controlled by carbon diffusion. By increasing the time and temperature of tempering, the corrosion current density (i corr ) in the polarization curves decreased whereas the diameter of the semicircular arc in the Nyquist plots increased, which implies higher corrosion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The values of corrosion potential, the corrosion current, and the vortex potential for all measurements along with their standard deviations are presented in Table 4. Using the polarization curve, current density is determined by the Tafel extrapolation method [46][47][48]. Extrapolation is generally conducted using both cathodic and anodic branches of the polarization curve.…”
Section: Eis Resultsmentioning
confidence: 99%
“…The values of corrosion potential, the corrosion current, and the vortex potential for all measurements along with their standard deviations are presented in Table 4. Using the polarization curve, current density is determined by the Tafel extrapolation method [46][47][48]. Extrapolation is generally conducted using both cathodic and anodic branches of the polarization curve.…”
Section: Eis Resultsmentioning
confidence: 99%
“…A further study has been carried out to determine the effect of tempering on the electrochemical corrosion properties of the Martensitic grade AISI4130, indicating that the heat treatment process leads to a decreased electrochemical corrosion current (IC) against 3.5% NaCl water saline solution. It also showed that the increased surface microhardness of the heat-treated material demonstrates the heat treatment process' ability to improve the electrochemical corrosion and abrasive wear resistance of the material [21]. Previous studies discussed the advantage of the tempering process after quenching step on the mechanical properties of the heat-treated carbon steel.…”
Section: Introductionmentioning
confidence: 92%
“…The material used in the current work was a low alloy carbon steel, the AISI 4130, containing chromium and molybdenum as strengthening agents. It is one of the most widely used low alloy steels for various applications due to its improved corrosion and wear resistance, hardenability, and enhanced mechanical strength for high temperature applications [25][26][27][28][29]. When designing and selecting low-alloy steels used in various equipment and structures, elastic and damping properties play a key role.…”
Section: Of 18mentioning
confidence: 99%